RAPID CONFIRMATION OF TUBERCULOUS MENINGITIS IN CHILDREN BY LIQUID CULTURE MEDIA - Hannan, Abdul; Hafeez, Amna; Chaudary, Sadia; Rashid, Mariam (Journal of Ayub Medical College Abbottabad, 2010)
Background: Tuberculous meningitis (TBM) is an important and serious complication of tuberculosis (TB) related to high morbidity and mortality. Childhood TBM is a diagnostic dilemma as the clinical features are non-specific and cerebrospinal fluid (CSF) mycobacterial count is low. The diagnosis is made mostly on clinical grounds, CSF analysis and radiological findings and treatment is initiated before the culture results arrive. These non-specific rapid diagnostic tools may be misleading resulting in over diagnosis or misdiagnosis. The conventional way of establishing a definitive diagnosis of TBM is by solid-medium culture that requires 4-7 weeks which may often lead to injudicious exposure to hazards associated with anti-tuberculous therapy (ATT). Methods: This study was carried out at the Microbiology department of University Of Health Sciences Lahore. The aim of this study was to assess the reliability of clinical features and CSF analysis in diagnosing childhood TBM by utilizing BACTEC Mycobacterial Growth Indicator Tube (MGIT) 960 system as a rapid confirmatory tool. It was an observational study that included 100 CSF samples from suspected paediatric TBM cases. After carrying out the biochemical and cytological analysis the samples were subjected to Ziehl-Neelsen (ZN) staining and inoculated onto MGIT 960 system. The culture growths were tested for sensitivity to first line ATT. Results: Of the 100 samples inoculated, only 14 yielded a growth, thus emphasizing unreliability of clinical criteria to diagnose TBM. CSF biochemistry was found insignificant for the diagnosis of TBM (p=2.260). The CSF cytology, however, was found significant for diagnosing TBM (p=0.001).Conclusions: The study showed that BACTEC MGIT 960 can be effectively used as a rapid diagnostic tool for the diagnosis of extra pulmonary tuberculosis. Keywords: Mycobacterium tuberculosis, Cerebrospinal fluid, BACTEC MGIT 960, Tuberculous meningiti